PHYLOGENETIC ANALYSIS OF 16S RRNA OF A BARTONELLA SP. FROM CATTLE IN CEBU, PHILIPPINES - Ybañez, Adrian P.; Ybañez, Rochelle Haidee D. (Journal of Agriculture and Technology Management, 2016)
Bartonella sp. is a Gram-negative bacteria that can infect humans and animals, including livestock. In the Philippines, studies on the genus Bartonella in livestock have been limited. This study aimed to analyze a 16S rRNA fragment of Bartonella sp. previously obtained from cattle in Cebu, Philippines. The aforementioned DNA fragment is believed to be the first molecular evidence of Bartonella sp. detected in Philippine livestock. Phylogenetic analyses were performed using neighbor joining, maximum likelihood, and maximum parsimony. The studied sequence was found to be closest to Bartonella bovis (99.6%), followed by Bartonella schoenbuchensis (99.1%), Bartonella capreoli    (99.1%) and Bartonella chomelii (99.1%). It was least similar to Bartonella bacilliformis (97.6). On the other hand, phylogenetic analyses revealed that the obtained sequence consistently clustered with B. bovis regardless of the method used. More studies are needed to analyze the detected Bartonella sp. using other genes to further assess phylogenetic relationships and confirm the species identification, especially that it clustered with the pathogenic B. bovis .